(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article considers and analyzes the general state of physical education in the education system of the country, the effectiveness of the use of physical culture and recreation activities, taking into account the unfavorable environmental situation in some regions of the country. In order to strengthen and support the health of the younger generation, it was proposed that the implementation of health-improving physical culture through the development and implementation of evidence-based innovative technologies accelerate the transformation of the educational process.